Mariposas para los muertos - Liang, Diane Wei, 1966-; Diez, Lola; Liang, Diane Wei, 1966- (Madrid : Ediciones Siruela, 2011)
When Mei receives a call from the chief executive at Guanghua Record Company, she learns that one of Mr. Peng's top starlets--the beautiful pop star and troubled, mysterious Kaili--has been missing for four days. Mei must find the starlet while keeping up the record company's facade that nothing is amiss.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Mei, Wang -- (Fictitious character) -- Fiction; Women private investigators -- China -- Beijing -- Fiction; Sound recording industry -- China -- Beijing -- Fiction; Beijing (China) -- Fiction; Detective and mystery fiction; Electronic books